Effects of increasing dietary level of organic acids and nature-identical compounds on growth, intestinal cytokine gene expression and gut microbiota of rainbow trout (Oncorhynchus mykiss) reared at normal and high temperature. Issue 107 (December 2020) - Pelusio, Nicole Francesca; Rossi, Barbara; Parma, Luca; Volpe, Enrico; Ciulli, Sara; Piva, Andrea; D'Amico, Federica; Scicchitano, Daniel; Candela, Marco; Gatta, Pier Paolo; Bonaldo, Alessio; Grilli, Ester
Abstract: Organic acids (OA) and nature-identical compounds (NIC) such as monoterpenes and aldehydes are well-known growth and health promoters in terrestrial livestock while their application for fish production is recent and their mechanisms of action require further study. Hence, this study tested the increasing dietary level (D0, D250, D500, D1000; 0, 250, 500 and 1000 mg kg feed −1 respectively) of a microencapsulated blend containing citric and sorbic acid, thymol and vanillin over 82 days on rainbow trout to assess the effects on growth, feed utilization, intestine cytokine gene expression and gut microbiota (GM). Furthermore, the effects on intestinal cytokine gene expression and GM were also explored after one week at high water temperature (23 °C). OA and NIC improved specific growth rate (SGR) and feed conversion rate (FCR) during the second half (day 40–82) of the feeding trial, while at the end of the trial protein (PER) and lipid efficiency (LER) increased with increasing dietary level. GM diversity and composition and cytokine gene expression analysis showed no significant differences in fish fed with increasing doses of OA and NIC (82 days) demonstrating the absence of inflammatory activity in the intestinal mucosa. Although there were no statistical differences, GM structure showed a tendency in clustering D0 group separately from the other dietary groups and a trend towards reduction of Streptococcus spp. was observed in the D250 and D1000 groups. After exposure to high water temperature, lower GM diversity and increased gene expression of inflammatory intestinal cytokines were observed for both inclusions (D0 vs . D1000) compared to groups in standard condition. However, the gene up-regulation involved a limited number of cytokines showing the absence of a substantial inflammation process able to compromise the functional activity of the intestine. Despite further study should be conducted to fully clarify this mechanism, cytokines up-regulation seems to be concomitant to the reduction of the GM diversity and, particularly, to the reduction of specific lactic acid bacteria such as Leuconostoc . The application of the microencapsulate blend tested can be a useful strategy to improve growth and feed utilization in rainbow trout under normal temperature conditions. According to the results organic acids and nature-identical compounds did not revert the effects triggered by the increased temperature of water. Highlights: Dietary organic acid and nature-identical compounds improved growth in rainbow trout. No diet effect was observed on intestinal cytokines expression and gut microbiome. High water temperature up-regulated cytokines and reduced microbiome diversity. Diets did not revert the effects triggered by the increased temperature of water.